Factors associated with recurrent abortions at the Hospital Materno Infantil Showing Ferrari, Huanuco, 2018-2020 - Palma-Lozano, Diana (2020)
Objective. To determine the sociodemographic and clinical factors of recurrent abortion at the Hospital Materno Infantil Showing Ferrari, Huánuco, 2018-2020. Methods. An observational, retrospective and relational study was conducted in a cohort. The sample population was 572 women with a diagnosis of abortion attended at the Hospital, between October 2018 and December 2020. Women with ectopic pregnancy and complete abortions on admission to the hospital were excluded. The data collection technique was by documentary analysis through the Perinatal Information System. Results.A total of 572 (100%) women were included, 45.3 % (259) of cases were in the 18-29 years age group, 56.5% (323) were housewives and 64.9 % (371) were cohabiting women. Regarding clinical characteristics, 45.8% had more than three pregnancies, 21% and 22.4 % had post-procedural anemia and previous urinary tract infection, respectively, and 92.3% had curettage. The frequency of recurrent abortion was 32 %. Factors associated with a higher frequency for recurrent abortion were: being an adolescent p=0.000, housewife p=0.000, single p=0.000, two or more gestations p=0.000, blood transfusion p=0.001, preprocedural anemia p=0.010 and postprocedural anemia p=0.034. Conclusion. Recurrent abortion has a significant association with being an adolescent, housewife, single, having two or more pregnancies, blood transfusion, pre- and post- procedural anemia.